Da caverna à circulação: operações de produção de sentido em um acontecimento midiatizado - Santos, Mariane Ramos (Universidade do Vale do Rio dos Sinos, 2021)
From the issue of the mediatized event, we seek to understand how the narratives in circulation transform the event within the mediatization process, in particular the case of the Javalis Selvagens team, 12 teenagers and their coach, who were imprisoned for 18 days in the Tham Luang cave, in Thailand, in 2018. Before starting the analysis process, we relied on some authors to define and trigger concepts such as journalistic event (CHARAUDEAU, 2006; RODRIGUES 1993; QUERÉ 2005), event and mediatization (FRANÇA, 2012; FAUSTO NETO, 2010; HEPP, 2014; VERÓN, 2014; FERREIRA; ROSA 2011; GOMES, 2016). After the survey of materials, with a view to investigating this process, we observed a small circuit built around the case, through the observables - an audiovisual production (documentary), journalism (reports) and comments from social actors on Facebook and Youtube – and of the axes, media circulation (VERÓN, 2004; BRAGA, 2012; FERREIRA, 2013; ROSA, 2019; FAUSTO NETO, 2010; SOSTER, 2017); narratives in mediatization (BARTHES, 2011; ROSA, 2016; GONÇALVES, 2014; SQUIRE, 2014; RESENDE, 2009; SOSTER, 2015), space time (VERÓN, 2004; CARLÓN, 2020; RICOEUR, 1994), memory (RICOEUR, 2007; MARQUES, 2017; ROSA, 2012; GOMES, 2001) and images and imagery (ROSA, 2017; KAMPER, 2018), it was possible to analyze and identify the narratives mediatized in the objects, and how each one contributes to a new event appearing. From inferences and articulations between empirical object and theory, we were able to identify the transformation of the media event into mediatized event and its remodeling throughout its permanence in circulation. We also signaled as results the complexification of the meanings of the narratives from the development of mediatization operations by different agents that co-produce the event, linking it to other precedents and also to those to come.
Keywords: Acontecimento; Narrativas; Midiatização; Circulação; Tailândia; Event; Narratives; Mediatization; Circulation; Thailand; ACCNPQ::Ciências Sociais Aplicadas::Comunicação